Remotely sensed spatial heterogeneity as an exploratory tool for taxonomic and functional diversity study - Rocchini, Duccio; Bacaro, Giovanni; Chirici, Gherado; Da Re, Daniele; Feilhauer, Hannes; Foody, Giles M.; Galluzzi, Marta; Garzon-Lopez, Carol X.; Gillespie, Thomas W.; He, Kate S.; Lenoir, Jonathan; Marcantonio, Matteo; et al. (Elsevier, 2017)
Assessing biodiversity from field-based data is difficult for a number of practical reasons: (i) establishing the total number of sampling units to be investigated and the sampling design (e.g. systematic, random, stratified) can be difficult; (ii) the choice of the sampling design can affect the results; and (iii) defining the focal population of interest can be challenging. Satellite remote sensing is one of the most cost-effective and comprehensive approaches to identify biodiversity hotspots and predict changes in species composition. This is because, in contrast to field-based methods, it allows for complete spatial coverages of the Earth's surface under study over a short period of time. Furthermore, satellite remote sensing provides repeated measures, thus making it possible to study temporal changes in biodiversity. While taxonomic diversity measures have long been established, problems arising from abundance related measures have not been yet disentangled. Moreover, little has been done to account for functional diversity besides taxonomic diversity measures. The aim of this manuscript is to propose robust measures of remotely sensed heterogeneity to perform exploratory analysis for the detection of hotspots of taxonomic and functional diversity of plant species.